Clinical evaluation of β‐tubulin real‐time PCR for rapid diagnosis of dermatophytosis, a comparison with mycological methods. Issue 10 (12th July 2017) - Motamedi, Marjan; Mirhendi, Hossein; Zomorodian, Kamiar; Khodadadi, Hossein; Kharazi, Mahboobeh; Ghasemi, Zeinab; Shidfar, Mohammad Reza; Makimura, Koichi
Summary: Following our previous report on evaluation of the beta tubulin real‐time PCR for detection of dermatophytosis, this study aimed to compare the real‐time PCR assay with conventional methods for the clinical assessment of its diagnostic performance. Samples from a total of 853 patients with suspected dermatophyte lesions were subjected to direct examination (all samples), culture (499 samples) and real‐time PCR (all samples). Fungal DNA was extracted directly from clinical samples using a conical steel bullet, followed by purification with a commercial kit and subjected to the Taq‐Man probe‐based real‐time PCR. The study showed that among the 499 specimens for which all three methods were used, 156 (31.2%), 128 (25.6%) and 205 (41.0%) were found to be positive by direct microscopy, culture and real‐time PCR respectively. Real‐time PCR significantly increased the detection rate of dermatophytes compared with microscopy (288 vs 229) with 87% concordance between the two methods. The sensitivity, specificity, positive predictive value, and negative predictive value of the real‐time PCR was 87.5%, 85%, 66.5% and 95.2% respectively. Although real‐time PCR performed better on skin than on nail samples, it should not yet fully replace conventional diagnosis.